Acidentes por queimadura grave em usuários de hospitais municipais de urgência do município de São Luís – Ma:análise quantitativa e qualitativa - MOCELIN, Paulo Roberto (2018)
ABSTRACT Burns represent an important global public health problem due to its morbidity and high potential to evolve with disabling sequelae. The outcome of treatment depends on an appropriate initial care followed by specialized care. Maranhão does not have a Burn Treatment Center and the service is provided in emergency and emergency municipal hospitals in São luís. The objective of this research was to assess the serious burns treated in these hospitals, to carry out a normative evaluation of the care, to identify the most affected population and to characterize it in the context of the vulnerability. It is a descriptive, prospective, quantitative and qualitative study. The first article was population-based, with a quantitative approach, carried out in two stages. In the first, a structured questionnaire was applied with 87 patients, followed by clinical evaluation and data collection of medical records. In the second, a semistructured questionnaire was applied with 101 emergency physicians providing care. The data gave the dimension of the aggravation and the behaviors adopted in the care, which were evaluated using the protocol of the Ministry of Health as a parameter. In the second article the approach was qualitative. The quantitative size of the burn phenomenon in the population with the highest frequency totaling 38 children. The ones with the highest severity (8) were selected for qualitative evaluation. The parents were interviewed following a script with questions about the perception of the circumstances of the accident, notions of risk and prevention and experience from the occurrence and treatment. The interviews were transcribed, categorized, submitted to the analysis of thematic content, recommended by Bardin, and contextualized according to the vulnerability. It was identified a high prevalence of burns in children, especially by scalds, in the home environment, with predominance of males. There was a lack structure of the institutions that provide care and lack of compliance with the protocol established by the MS. The victims are predominantly low-income and educated, with no access to information on risk and protective measures and with limited ability to respond adequately to the accident. It is imperative to adopt specific public policies for burns and prevention campaigns with parents and in schools in the municipality.